The meaning of fatherhood to men in relationships with female sex workers in Kampala, Uganda: The struggle to model the traditional parameters of fatherhood and masculinity. - Martin Mbonye; Godfrey Siu; Janet Seeley (PLoS ONE)
Many women who engage in sex work in sub-Saharan Africa become pregnant, often unintentionally. There is limited attention paid to the experiences of fathers of children born to women engaged in sex work. We examine the meaning of fatherhood to these men, the significance of children, and how they navigate the economic and cultural challenges of fatherhood in this context. Analysis is based on ethnographic data from 13 men who identified as intimate long-term partners of female sex workers (FSW) in Kampala City, Uganda. Our findings illustrate how men who have children with FSW struggled to model the traditional parameters of fatherhood and masculinity. We found that men who had children with FSW faced hurdles fitting within the social construction of ideal fatherhood. Accepting fatherhood often started with doubts over the pregnancy because of the multiple partnerships of women. Men who only saw themselves as clients struggled to adjust to being fathers because of their perceptions of the social implications of fathering a child with a FSW. Integration of mothers who were also sex workers into the man's extended family was a challenge because of the fear of negative reactions from family members. However, when men accepted their roles as fathers, they started seeing value in their children. Due to poverty, most of the men fell short of the societal measures of masculinity, but children transformed their social status before their society and family. The provider role often used to define good fathering was a challenge for men. However, the financial support from FSW partners softened the burden and facilitated the creation of a family environment constructed to the perceived standards of the broader society. Our findings provide insights into the state of parenting among FSW and their partners which can guide interventions that are tailored to their unique circumstances.